Perancangan Aplikasi Tiket Wisata Air Terjun Berbasis Web Menggunakan Metode Agile Scrum - Hafa Leny Tahta Syarifah; Cempaka Ananggadipa Swastyastu; Ratna Nur Tiara Shanty (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The rapid advancement of information technology has become a key driver of digital transformation across various sectors, including tourism. The utilization of technology in managing tourist destinations can enhance service efficiency and improve the quality of information provided to visitors. One of the challenges faced by Dlundung Waterfall Tourism is the ticket booking process, which is still carried out manually, resulting in long queues, data recording errors, and the risk of information loss during data recap. These conditions lead to inefficient data management and hinder efforts to improve service quality for tourists. This study aims to design and develop a web-based ticket booking application for Dlundung Waterfall Tourism to assist administrators in automating service processes. In its development, the Agile Scrum methodology is employed, as it can quickly adapt to changing requirements through iterative stages. Additionally, the Laravel framework is chosen as the primary development foundation because it offers a robust architectural structure, strong security features, and convenience in data management and organized feature development. The application includes several main features, such as the home page, online ticket booking, destination information, payment, my tickets, and contact.